2009
DOI: 10.1038/clpt.2008.261
|View full text |Cite
|
Sign up to set email alerts
|

Pro32Thr Polymorphism of Inosine Triphosphate Pyrophosphatase Gene Predicts Efficacy of Low-Dose Azathioprine for Patients With Systemic Lupus Erythematosus

Abstract: We evaluated the relationship between the efficacy of low-dose azathioprine (AZA) therapy and the inosine triphosphate pyrophosphatase (ITPA) 94C>A (Pro32Thr) polymorphism in patients with systemic lupus erythematosus (SLE). We performed a multiple regression analysis to assess the influence of various factors on the reduction in SLE disease activity index (SLEDAI) scores. The ITPA 94C>A polymorphism had the highest correlation with the change in SLEDAI score (r = 0.354, P = 0.006).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…Therefore, Asians who have a low frequency of TPMT variant alleles may be more susceptible to toxicity from mercaptopurine related to ITPA variant alleles, while Hispanic patients have a high frequency of TPMT variant alleles and low frequency of the ITPA, indicating that toxicity in this population may be more easily related to TPMT [53]. Indeed, recent studies done in Japanese patients treated with mercaptopurine or azathioprine, a mercaptopurine pro-drug, for systemic lupus erythematosus (SLE) or for IBD have demonstrated that variant alleles of ITPA are highly correlated with a better response to the thiopurines in SLE [63] or are closely related to the adverse reactions of azathioprine/ mercaptopurine [64], supporting a particularly relevant role of this polymorphism on mercaptopurine pharmacogenetics in the Asian population.…”
Section: Itpa Enzyme: Biological Functions and Effect On Mercaptopurimentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, Asians who have a low frequency of TPMT variant alleles may be more susceptible to toxicity from mercaptopurine related to ITPA variant alleles, while Hispanic patients have a high frequency of TPMT variant alleles and low frequency of the ITPA, indicating that toxicity in this population may be more easily related to TPMT [53]. Indeed, recent studies done in Japanese patients treated with mercaptopurine or azathioprine, a mercaptopurine pro-drug, for systemic lupus erythematosus (SLE) or for IBD have demonstrated that variant alleles of ITPA are highly correlated with a better response to the thiopurines in SLE [63] or are closely related to the adverse reactions of azathioprine/ mercaptopurine [64], supporting a particularly relevant role of this polymorphism on mercaptopurine pharmacogenetics in the Asian population.…”
Section: Itpa Enzyme: Biological Functions and Effect On Mercaptopurimentioning
confidence: 98%
“…This indicates that if mercaptopurine doses are not individualized based on TPMT genotype, then TPMT will be the predominant determinant of severe hematopoietic toxicity, whereas if doses are adjusted for TPMT, then ITPA has a significant influence on the risk of febrile neutropenia. All previous studies evaluating the role of ITPA polymorphism on the toxicity of thiopurine have been done in patients with IBD, with contradictory results [45][46][47][48][49][50][51][52]54,63]. Most of these studies considered patients taking a dose of mercaptopurine that was not systematically adjusted on the basis of TPMT genotype and our findings indicate that this is probably the reason why the effect of ITPA was not consistent in these previous studies.…”
Section: Genetic Polymorphisms Of Itpa and Mercaptopurine Toxicitymentioning
confidence: 99%
“…Following description of the enzyme defect, the low TPMT enzyme activity was found to be predominantly due to three common variants in the TPMT gene 73 74. Inosine triphosphate pyrophosphatase (ITPA) is an enzyme that prevents accumulation of thioinosine metabolites by converting them to 6-thioinosine monophosphate, and deficiency of this enzyme has also been reported in patients with adverse reactions to thiopurine compounds 7577. IPTA deficiency is usually due to a polymorphism of ITPA (Pro32Thr) more common in Asian populations (11–19%), than in other ethnic groups such as Caucasians, Hispanics and Africans (1–7%).…”
Section: Using Genetic Information In the Treatment Of Sle: Implicatimentioning
confidence: 99%
“…This polymorphism was associated with a better response to low-dose azathioprine in the treatment of systemic lupus erythematosus (Okada et al, 2009). Most recently, ITPA deficiency was found to protect against hemolytic anemia in hepatitis C patients treated with ribavirin (Fellay et al, 2010; Ochi et al, 2010; Sakamoto et al, 2010; Thompson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%